Second allogeneic stem cell transplant for aplastic anaemia: a retrospective study by the severe aplastic anaemia working party of the European society for blood and marrow transplantation. (25th August 2015) - Cesaro, Simone; de Latour, Regis Peffault; Tridello, Gloria; Pillon, Marta; Carlson, Kristina; Fagioli, Franca; Jouet, Jean‐Pierre; Koh, Mickey B. C.; Panizzolo, Irene Sara; Kyrcz‐Krzemien, Slawomira; Maertens, Johan; Rambaldi, Alessandro; et al.
Summary: We analysed the outcome of a second allogeneic haematopoietic stem cell transplant (alloHSCT) in 162 patients reported to the European Society for Blood and Marrow Transplantation between 1998 and 2009. Donor origin was a sibling in 110 and an unrelated donor in 52 transplants, respectively. The stem cell source was bone marrow in 31% and peripheral blood in 69% of transplants. The same donor as for the first alloHSCT was used in 81% of transplants whereas a change in the choice of stem cell source was reported in 56% of patients, mainly from bone marrow to peripheral blood. Neutrophil and platelet engraftment occurred in 85% and 72% of patients, after a median time of 15 and 17 days, respectively. Grade II‐IV acute graft‐versus‐host disease (GVHD) and chronic GVHD occurred in 21% and 37% of patients, respectively. Graft failure (GF) occurred in 42 patients (26%). After a median follow‐up of 3·5 years, the 5‐year overall survival (OS) was 60·7%. In multivariate analysis, the only factor significantly associated with a better outcome was a Karnofsky/Lansky score ≥80 (higher OS). We conclude that a second alloHSCT is feasible rescue option for GF in SAA, with a successful outcome in 60% of cases.